Instructional use of counting media to improve mathematical conceptual understanding in elementary education - Maulinah, Maulinah (Science Center Group, 2025)
Background: Mathematical conceptual understanding in elementary education remains a critical concern, particularly in fostering students’ ability to connect procedural fluency with conceptual reasoning. Instructional media, especially counting-based manipulatives and digital tools, are increasingly recognized as effective strategies to enhance numeracy learning in primary classrooms. However, empirical evidence examining their structured implementation and measurable impact on conceptual mastery is still limited. Objective: This study aimed to examine the effectiveness of instructional use of counting media in improving mathematical conceptual understanding among elementary school students. Methods: A quasi-experimental design with a pre-test and post-test control group was employed involving 56 elementary students divided into experimental and control groups. The experimental group received mathematics instruction using structured counting media, while the control group received conventional instruction. Data were collected through validated conceptual understanding tests and classroom observations. Statistical analyses included independent samples t-test, normalized gain (N-gain), and effect size (Cohen’s d) to determine the magnitude of improvement. Results: The findings revealed that the experimental group achieved significantly higher post-test scores compared to the control group (p < 0.01). The normalized gain score of the experimental group indicated a moderate-to-high improvement category, while the control group demonstrated low improvement. The calculated effect size (d = 1.56) reflected a large educational impact. Classroom observations further indicated increased student engagement, improved conceptual explanation ability, and enhanced confidence in problem-solving activities. Conclusion: The instructional use of counting media significantly enhances mathematical conceptual understanding in elementary education. Structured integration of manipulative and interactive counting tools provides meaningful learning experiences that bridge concrete and abstract mathematical thinking. The study supports the adoption of counting-based instructional media as an evidence-based strategy to strengthen conceptual mathematics learning in primary schools.